FISHERY RESOURCES OF THE RAMESWARAM ISLAND - Krishnamurthi, B (Indian Journal of Fisheries, 2015)
Annually on an average of 1,585-53 tons of fish were landed in the Island. Fish catches were generally poor during the winter months. This was due to the cessation of the Boat-Seine fishing. Altogether 33 species were recorded during the two years. But only 12 species, viz., L. splendens, S. guttatus, C. dorab, S. gibbosa, L. lactarius, Scoliodon sp., D. hasselti, Caranx sp., H. georgii, Arius sp., G. filamentosus and R. canagurta were of fishery importance. L. splendens topped the Ust during both years with S. guttatus holding the second rank. The seasonal fluctuations of these fishes are indicated. Very little of fish is consumed within the Island. Consequently much of it is exported as cured fish to various places such as Ceylon, Madura, Paramakudi, etc.